Assessment of the novel online delineation workshop dummy run approach using FALCON within a European multicentre trial in cervical cancer (RAIDs). Issue 1 (July 2017) - Rivin del Campo, Eleonor; Rivera, Sofia; Martínez-Paredes, María; Hupé, Philippe; Slocker Escarpa, Andrea; Borget, Isabelle; Mazeron, Renaud; Scholl, Suzy; Palacios Eito, Amalia; Haie-Meder, Christine; Chargari, Cyrus; Deutsch, Eric
Abstract: Background and purpose: Online delineation workshops (ODW) permit training of geographically dispersed participants. The purpose is to evaluate the methodology of an ODW using FALCON to harmonize delineation within a European multicentre trial on locally advanced cervical cancer (LACC). Material and methods: Two ODW included 46 clinicians (14 centres). Clinicians completed baseline (C1), guideline (C2) and final contours (C3) for external beam radiotherapy (EBRT) and brachytherapy (BT) for LACC. Interobserver and intraobserver variability was evaluated quantitatively (using the DICE index) and qualitatively compared to expert contours. Results: Nine clinicians submitted for EBRT and BT for C1–C3. Thirty-two sent any contour. Interobserver quantitative comparisons for EBRT showed significant improvement for C2 vs. C1 for bowel, CTV node, CTV-p and GTV node with significant detriment for GTV node (C3 vs. C1; C2), CTV-p (C3 vs. C2) and bowel (C3 vs. C2), showing in general an improvement in C2 vs. C1, with a detriment in C3 vs. C2 for two target volumes and an organ at risk. For BT there was significant improvement for C2 vs. C1 for bladder, GTV, HR-CTV and IR-CTV, with significant detriment for bladder (C3 vs. C2), thus overall improvement in C2 vs. C1, with only a detriment in C3 vs. C2 for bladder. Centres using MRI imaging for BT contouring did significantly better in the BT case for HR-CTV than those which used other techniques (C2 vs. C1: p  < 0.005; C3 vs. C1: p  = 0.02). Intraobserver quantitative comparisons showed significant improvement contouring a region of interest between C2 vs. C1, C3 vs. C1 and C3 vs. C2 for EBRT and between C2 and C1 for BT. Conclusions: ODW offer training, initial contouring harmonization and allow assessment of centres.